PENGARUH PEMBELAJARAN ETNOMATEMATIKA BLITAR TERHADAP EFIKASI DIRI MATEMATIS MATERI OPERASI HITUNG PERKALIAN SISWA SEKOLAH DASAR - Siti Nur Azizah; Surayanah; Rika Mellyaning Khoiriya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to investigate the implementation and impact of ethnomathematics-based learning on the mathematics self-efficacy of elementary school students in learning multiplication. This research approach uses quantitative methods with a quasi-experimental design. Data were collected using interview sheets, questionnaires, and observation. The research population comprised 40 fourth-grade students at MI Al Azhar Bening, with 20 students assigned control and 20 students to the experimental group. Data analysis was conducted using descriptive statistics and inferential statistics, including normality tests, homogeneity tests, and an independent sample t-test. The results of the classroom experiment, carried out over three meetings, showed an average response score of 95,5%, indicating that the overall stages of ethnomathematics-based learning ware implemented effectively. The Independent Sample T-Test results showed that sig. (2-tailed) ≤ 0,05, specifically 0,009 ≤ 0,5, leading to the acceptance of Ha and the rejection of H0. This means that ethnomathematics-based learning has a positive effect on mathematics self-efficacy. Thus, it can be concluded that the use of ethnomathematics-based learning positively influences the mathematics self-efficacy of fourth-grade students at MI Al Azhar Bening.